Management of Severe Traumatic Brain Injury: A Single Institution Experience in a Middle-Income Country - Basha, Ahmed Kamel; Mahmoud, Mohamed Ashraf; Al Ashwal, Mohamed Ismail; Aglan, Osama; ElShawady, Sherif Bahaa; Abdel-Latif, Assem Mounir; Elsayed, Ahmed M.; AbdelGhany, Walid (Frontiers in Surgery, 2021)
Introduction: Severe traumatic brain injury (TBI) is a major public health problem usually resulting in victims’ mortality or severe disabling morbidities. Intracranial pressure (ICP) monitoring is recently recognized as an imperative modality in the management of severe TBI, while growing evidence; based on randomized controlled trials (RCTs); suggests that ICP monitoring does not affect the outcome when compared to clinical and radiological data- based management. Also, ICP monitoring carries a considerable risk of intracranial infection that cannot be overlooked. The aim of this study is to assess our current local institutional management of severe TBI using non-invasive ICP monitoring for potential need to change our management strategy. Methods: We retrospectively reviewed our data of TBI from June 2019 through January 2020. Patients with severe TBI were identified. Their demographics, Glasgow Coma Score (GCS) at presentation and treatments received were extracted from the charts. Glasgow outcome scale extended (GOS-E) at 6 months was assessed for the patients. Results: Twenty patients with severe TBI were identified on chart review. Ten patients received only medical treatment measures to lower the ICP, while the other 10 patients had surgical interventions. In 1 patient, ventriculostomy tube was inserted to monitor ICP and to drain cerebrospinal fluid (CSF). This was complicated by ventriculostomy associated infection (VAI) and was removed. In our cohort, total mortality rate was 40%. The average GOS-E for the survivor patients managed without ICP monitoring based on the clinical and radiological data was 6.2 at 6 months follow up. The six- month overall good outcome, based on GOS-E was 33.3%. Conclusion: Although recent guidelines advocate for the use of ICP monitoring in management of severe TBI, they remain underutilized in our practice due to many factors. EVDs were mainly used to drain CSF however, the higher rates of VAIs in our institution compared to the literature-reported rates is not in favor of the use for ICP monitoring. We recommend to do a comparative study between our current practice using clinical and radiological based management and subdural or intraparenchymal bolts. More structured randomized controlled trials are needed to validate these findings in our setting.